Small Bowel Carcinoma in the Setting of Inflammatory Bowel Disease - Bhatt, Himani; Mathis, Kellie L. (Clinics in Colon and Rectal Surgery, 2023)
Small bowel carcinomas are rare in the general population, but the incidence is increasing. Patients with inflammatory bowel diseases (IBDs) are at significantly higher risk of small bowel adenocarcinomas than their non-IBD counterparts, with Crohn's patients having at least a 12-fold increased risk and ulcerative colitis patients with a more controversial and modest 2-fold increased risk compared with the general population. IBD patients with small bowel carcinomas present with nonspecific symptoms that overlap with typical IBD symptoms, and this results in difficulty making a preoperative diagnosis. Cross-sectional imaging is rarely diagnostic, and most cancers are found incidentally at the time of surgery performed for an IBD indication. As such, most small bowel carcinomas are found at advanced stages and carry a poor prognosis. Oncologic surgical resection is the treatment of choice for patients with locoregional disease with little evidence available to guide adjuvant therapy. Patients with metastatic disease are treated with systemic chemotherapy, and surgery is reserved for palliation in this population. Prognosis is poor with few long-term survivors reported.
Keywords: small bowel adenocarcinoma; small bowel cancer; inflammatory bowel diseases; Crohn's disease; ulcerative colitis